2022
DOI: 10.1186/s12916-022-02491-1
|View full text |Cite
|
Sign up to set email alerts
|

Single nucleotide polymorphism genes and mitochondrial DNA haplogroups as biomarkers for early prediction of knee osteoarthritis structural progressors: use of supervised machine learning classifiers

Abstract: Background Knee osteoarthritis is the most prevalent chronic musculoskeletal debilitating disease. Current treatments are only symptomatic, and to improve this, we need a robust prediction model to stratify patients at an early stage according to the risk of joint structure disease progression. Some genetic factors, including single nucleotide polymorphism (SNP) genes and mitochondrial (mt)DNA haplogroups/clusters, have been linked to this disease. For the first time, we aim to determine, by us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 67 publications
0
8
0
Order By: Relevance
“…His team has been working on a series of studies on the pathogenesis, risk factors, biomarkers, and treatment of OA. In a recent study, they identified single nucleotide polymorphism genes and mitochondrial DNA haplogroups as biomarkers for early prediction of the progression of knee OA through machine learning ( Bonakdari et al, 2022 ; Martel-Pelletier and Pelletier, 2022 ). Highly cited literature can be considered the most valuable and influential research in the field, so new researchers can read these papers before further research ( Table 5 ; Figure 4 ).…”
Section: Discussionmentioning
confidence: 99%
“…His team has been working on a series of studies on the pathogenesis, risk factors, biomarkers, and treatment of OA. In a recent study, they identified single nucleotide polymorphism genes and mitochondrial DNA haplogroups as biomarkers for early prediction of the progression of knee OA through machine learning ( Bonakdari et al, 2022 ; Martel-Pelletier and Pelletier, 2022 ). Highly cited literature can be considered the most valuable and influential research in the field, so new researchers can read these papers before further research ( Table 5 ; Figure 4 ).…”
Section: Discussionmentioning
confidence: 99%
“…A recent study by Bonakdari et al . 222 evaluates whether eight single nucleotide polymorphism genes ( TP63 , FTO , GNL3 , DUS4L , GDF5 , SUPT3H , MC2FL , and TGFA ) and mitochondrial DNA haplogroups (H, J, T, Uk, and others) and clusters (HV, TJ, KU, and C-others), in addition to two risk factors (age and body mass index), could predict early knee OA structural progressors. The Jamshidi et al .…”
Section: Prediction Of Knee Osteoarthritis Diagnosis and Prognosis Us...mentioning
confidence: 99%
“…It has been implicated in multiple bioprocesses, including cell proliferation, differentiation, and cell cycle regulation. [116][117][118] GNL3 belongs to the GTP-binding protein family, containing an MMRHSR1 domain. 119 GNL3 is abundantly expressed in bone marrow mesenchymal stem cells (BM-MSCs) and is closely related to the differentiation of chondrocytes.…”
Section: Ythdf2 and Ythdc2mentioning
confidence: 99%
“…119 GNL3 is abundantly expressed in bone marrow mesenchymal stem cells (BM-MSCs) and is closely related to the differentiation of chondrocytes. [116][117][118] Recently, both human and animal studies found that GNL3 were significantly reduced in knee tissues of OA samples compared with non-OA samples. However, the potential mechanism underlying aberrant GNL3 expression in OA remains unclear.…”
Section: Ythdf2 and Ythdc2mentioning
confidence: 99%
See 1 more Smart Citation